PENGARUH PERHATIAN ORANG TUA, KONSEP DIRI, PERSEPSI TENTANG MATEMATIKA TERHADAP HASIL BELAJAR MATEMATIKA MELALUI MOTIVASI BELAJAR SISWA KELAS VIII SMP NEGERI DI KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA - Muhammad Awal Nur (MATEMATIKA DAN PEMBELAJARAN, 2016)
Learning outcomes of mathematics is a benchmark of high or low the quality of mathematics learning process. There are numerous factors which influence high or low learning outcomes of mathematics. However, the scope of study is on parents’ attention, self concept, and perception on mathematics and learning motivation. The study aims at discovering the influence of parents’ attention, self-concept, and perception on mathematics toward learning outcome of mathematics directly and indirectly through learning motivation. The study is an ex-post facto which casual in nature. The populations of the study were 447 grade VIII students of public junior high school at Ujung Loe subdistrict in Bulukumba district of academic years 2012/2013 with as many as 204 samples. Technique used in selecting the samples was equal size random sampling. The instrument used for the study were (1) scale of parents’attention, (2) scale of self concept, (3) scale of perception on mathematics, (4) scale of learning motivation and test of mathematics learning outcomes. Data were analyzed uing descriptive statistics analysis and SEM (Structural Equation Modelling) analysis. The results of the study indicate that (1) most of grade VIII students have parents’ attention, self concept, learning motivation which are in high categories, perception on mathematics is in good category. whereas, learning outcomes of mathematics is in fair category; (2) parents’ attention, self concept, and perception on mathematics gave positive and significant influence toward students’ learning motivation; (3) parents’ attention, self concept, perception on mathematics and learning motivation gave positive and significant influence toward learning outcomes of mathematics; (4) parents’ attention gave positive and significant influence directly through learning motivation toward learning outcomes of mathematics; (5) self-concept gave positive and significant influence directly through learning motivation toward learning outcomes of mathematics and (6) perception on mathematics gave positive and significant influence directly through learning motivation toward learning outcomes of mathematics Key words : Learning Outcomes of Mathematics, Learning Motivation, Parents’ Attention, Self Concept and Perception on Mathematics